2012
DOI: 10.1590/s0102-86502012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal healing in rats submitted to ethanol ingestion

Abstract: . Mentor, designed the protocol and critical review. ABSTRACT PURPOSE:To study the effect of alcoholism on intestinal healing and postoperative complications in rats. METHODS:One hundred and sixty rats were divided into two groups: control and treated. The control group received water and the treated group 30% ethanol. After 180 days, colotomy with anastomosis were performed. After, the groups were divided into four subgroups: 20 rats for study at the following moments: 4 th , 7 th , 14 th and 21 st postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
(48 reference statements)
0
7
0
1
Order By: Relevance
“…Although the high incidence of chronic lung disease in alcoholics has been accepted and documented, little is known about the effects of alcohol on the lungs. The interrelation between smoking and body weight 1 and alcohol consumption and body weight 2,3 has been consolidated by several studies; however, none of these have considered the combination of both drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the high incidence of chronic lung disease in alcoholics has been accepted and documented, little is known about the effects of alcohol on the lungs. The interrelation between smoking and body weight 1 and alcohol consumption and body weight 2,3 has been consolidated by several studies; however, none of these have considered the combination of both drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Both alcohol and sepsis are known to lead to weight loss after surgery, and their combination diminished the post-operative body mass in this study, and even at the 7 POD that weight wasn’t recovered [13,14]. Sepsis leads to a consumptive syndrome due to the inflammation and alcohol intake is responsible for malnutrition because of intestinal malabsorption and is also responsible for body fat reduction [13,14].…”
Section: Discussionmentioning
confidence: 88%
“…Pereira et al 9 has shown that a model of chronic alcohol abuse in rats is associated with lower weight gain, impaired intestinal healing (as demonstrated by significantly lower bowel anastomosis breaking strength), and higher postoperative complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that acute alcohol exposure shortly before surgery would be a risk factor for impaired wound healing of the colonic anastomosis, based on results from other experimental studies [9][10][11][12] . However, in those studies, alcohol exposure followed different patterns.…”
Section: Introductionmentioning
confidence: 99%